Humanity as a Duty to Oneself - Adeniyi Fasoro, Sunday (Con-Textos Kantianos. International Journal of Philosophy, 2019)
This paper analyses the thorny interpretative puzzle surrounding the connection between humanity and the good will. It discusses this puzzle: if the good will is the only good without qualification, why does Kant claim that humanity is something possessing an absolute value? It explores the answers to this question within Kantian scholarship; answers that emanate from a commitment to the human capacity for freedom and morality and to actual obedience to the moral law. In its final analysis, it endorses Richard Dean’s good will reading as the most reflective of Kant’s ethics. It claims that in order for a person to reach the moral ideal of acting rightly and giving priority to moral law, he must always honour his duties to himself. Accordingly, it argues that before a person can be deemed as an object of respect, he must first respect the right of humanity in his own person.